RASS‐Enabled S/P−C and S−N Bond Formation for DEL Synthesis. Issue 19 (11th March 2020) - Flood, Dillon T.; Zhang, Xuejing; Fu, Xiang; Zhao, Zhenxiang; Asai, Shota; Sanchez, Brittany B.; Sturgell, Emily J.; Vantourout, Julien C.; Richardson, Paul; Flanagan, Mark E.; Piotrowski, David W.; Kölmel, Dominik K.; et al.
Abstract: DNA encoded libraries (DEL) have shown promise as a valuable technology for democratizing the hit discovery process. Although DEL provides relatively inexpensive access to libraries of unprecedented size, their production has been hampered by the idiosyncratic needs of the encoding DNA tag relegating DEL compatible chemistry to dilute aqueous environments. Recently reversible adsorption to solid support (RASS) has been demonstrated as a promising method to expand DEL reactivity using standard organic synthesis protocols. Here we demonstrate a suite of on‐DNA chemistries to incorporate medicinally relevant and C−S, C−P and N−S linkages into DELs, which are underrepresented in the canonical methods. Abstract : DNA encoded libraries (DEL) have shown promise as a valuable technology for democratizing the hit discovery process. A suite of on‐DNA chemistries is demonstrated to incorporate medicinally relevant C−S, C−P and N−S linkages into DELs, which are underrepresented in the canonical methods.